(untitled) (Journal of Human Sciences, 2026)
This study aims to examine the historical grounding and both ancient and contemporary applications of one of the most important legal maxims in regulating scattered subsidiary issues in the chapter on felonies. The research problem lies in determining the liability resulting from both the direct actor and the instigator (causer) when they concur, and investigating cases where financial liability (guarantee) shifts from the direct actor to the instigator, as well as cases where they share liability. Furthermore, it explores the extent to which this maxim addresses past events and modern, emerging contemporary issues. To achieve the objectives of the study and answer these questions, the descriptive and analytical methodology was adopted, while adhering to the recognized scientific research methodology, which led to reaching findings that fulfill the purpose of this study.